1976
DOI: 10.1056/nejm197612022952303
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Survival and Morphology in Homocystinuria Due to Cystathionine Synthase Deficiency

Abstract: In homocystinuria due to cystathionine synthase deficiency thromboembolism is a major cause of mortality and morbidity. Recent studies by others identified an abnormally shortened platelet survival and increased platelet vacuolization in patients with homocystinuria. When we studied six additional patients, however, we found the platelet survival to be within normal limits for each. The mean survival (+/-1 S.D.) was 9.75+/-0.94 days (normal, 9.27+/-1.06). In addition, platelets from five patients with homocyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
2

Year Published

1980
1980
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(18 citation statements)
references
References 21 publications
0
16
0
2
Order By: Relevance
“…McDonald and colleagues first demonstrated increased platelet "stickiness" in the blood of homocystinurics, and by the addition of homocystine to plasma ( 13). Changes in platelet adhesiveness, however, have not been confirmed subsequently by other groups (54)(55)(56). Several groups have also failed to demonstrate aggregation of platelets by homocystine (13,15,16).…”
Section: Discussionmentioning
confidence: 99%
“…McDonald and colleagues first demonstrated increased platelet "stickiness" in the blood of homocystinurics, and by the addition of homocystine to plasma ( 13). Changes in platelet adhesiveness, however, have not been confirmed subsequently by other groups (54)(55)(56). Several groups have also failed to demonstrate aggregation of platelets by homocystine (13,15,16).…”
Section: Discussionmentioning
confidence: 99%
“…Although Harker and colleagues 66 and Roulaud and co-workers 68 have reported reduced platelet survival in humans with homocystinemia, two other groups have been unable to confirm this observation. 69 ' 70 The reason for the discrepancy has not been established, although Hill-Zobel and co-workers 71 have suggested that differences in the methods used to analyze the platelet survival curves may be responsible.…”
Section: Chemical Injury Of Vessel Wallsmentioning
confidence: 99%
“…[7][8][9] In studies of platelet kinetics, a direct relationship was found between HCY concentration and platelet survival.…”
mentioning
confidence: 99%
“…5 In 1964, McDonald et al 6 concluded that HCY, both in vivo and in vitro, increased platelet stickiness associated with arterial and venous thrombosis, but this finding was not confirmed. [7][8][9] In studies of platelet kinetics, a direct relationship was found between HCY concentration and platelet survival. 10 Harker et al 7 found that increased platelet consumption in homocysteinemia was interrupted by dipyridamole, but not by heparin anticoagulation, and concluded that platelet thrombus formation on arterial surfaces denuded of endothelium, and not enhanced platelet reactivity, increased platelet consumption.…”
mentioning
confidence: 99%